2006
DOI: 10.1179/146532806x90565
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus infection: a major cause of acute hepatic failure in Thai children

Abstract: Improvements in sanitation and socio-economic status as well as the implementation of hepatitis B vaccine in the Extended Programme on Immunization (EPI) are likely to be the reasons for the observed absence of AHF caused by hepatitis A and B. The study showed that dengue infection, on the other hand, was a major cause of AHF in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 29 publications
4
41
3
6
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18] The liver enzymes were elevated in 45.4% of the cases similar to other studies 36.4%-96%. Commonest abdominal USG finding was gall bladder edema in 90.8% (156/174) of the cases.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14][15][16][17][18] The liver enzymes were elevated in 45.4% of the cases similar to other studies 36.4%-96%. Commonest abdominal USG finding was gall bladder edema in 90.8% (156/174) of the cases.…”
Section: Discussionsupporting
confidence: 72%
“…8 In recent studies from India and Thailand, dengue infection was the most important cause of acute hepatic failure in children contributing to 18.5% and 34.3% of the cases respectively. 15,16 Hence early recognition and prompt initiation of appropriate supportive treatment can decrease the morbidity and mortality. Most of the data reported on abnormal liver functions in dengue are retrospective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Kumar et al (4), dengue infection was responsible for 18.5% of acute hepatic failure of children in India. However, Poovorawan et al reported that 34.3% of their cases pediatric dengue infections were the major cause of acute hepatic failure in Thai children (9). Jaundice in dengue fever has been associated with fulminant hepatic failure and by itself is a poor prognostic factor (10).…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast to these adult studies, it is noteworthy that in dengue endemic countries, dengue may be an important cause of acute liver failure in children. 10,11 The mechanism of liver involvement in dengue infection is not clear and may explain a direct injury to liver cells or an immunological response. 12 AST is expressed in the heart, skeletal muscle, red blood cells, kidneys, brain and liver, while ALT is secreted primarily by the liver cells.…”
Section: Discussionmentioning
confidence: 99%